Application of Improved Methods for the Treatment of Vental Hernias (Texas Journal of Medical Science, 2022)
The treatment of hernias of the anterior abdominal wall occupies a special place in surgical practice, due to their wide distribution and the occurrence of undesirable consequences in the postoperative period. The study of the causes of these consequences showed that in modern hernia surgery, synthetic biomaterials are widely used, which are aimed at preventing complications and relapses. The method of operation carried out by us by combined hernioplasty allowed us to improve the results of surgical treatment and improve the quality of life of patients.